HUBUNGAN KARAKTERISTIK DAN DUKUNGAN KELUARGA LANSIA DENGAN KEJADIAN STROKE PADA LANSIA HIPERTENSI DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - Parida Hanum; Rahayu Lubis; Rasmaliah Rasmaliah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT             The rate of stroke incidence is about 200 per 100,000 people throughout the world. In Indonesia, 500,000 people suffer from stroke each year and 125,000 people. Effective family support is expected to be able to help the elderly to be treated their hypertension optimally in order to reduce the incidence of stroke. The objective of the research was to find out the correlation of the characteristics and support from the elderly family with the incidence of stroke in the elderly who suffered from hypertension at RSUP Haji Adam Malik, Medan.            The research is done by using cross sectional approach of 147 samples taken by using consecutive sampling. Independent variables were the characteristics (age, sex, ethnicity, education, occupation, and marital status) and dependent variable was stroke in the elderly who suffer from hypertension. The data were gathered by using primary and secondary and analyzed by using univatriate, bivatriate (chi square test), and multivatriate with multiple logistic regression analysis at α = 0.05.            The result of the research showed the variables which were correlated with the incidence of stroke were age (p=0.025), sex (p=0.011), emotional support (p<0.001), reward (p=0.07), and informational support (p<0.001). The variables which had the most dominant correlation with the incidence of stroke were informational support (p=0,001).             It is recommended that the hospital management increase health service and family support for the elderly in order that the elderly with hypertension can be prevented from stroke. Keywords: Characteristics, Support from the Elderly Families, Stroke in the Elderly with Hypertension